Effects of increasing levels of spray-dried blood meal and blood cells on nursery pig performance - James, B.J.; DeRouchey, Joel M.; Nelssen, Jim L.; Tokach, Michael D.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Three hundred fifty weanling pigs (initially 14.6 lbs and 17 ± 2 d of age) were used in a 19-d growth assay to determine the effects of increasing levels (2.5, 5.0, and 7.5%) of spray-dried blood meal or blood cells in the diet on growth performance. Overall, the dietary inclusion of both blood products improved ADG and feed efficiency. However, spray-dried blood meal improved ADG, ADFI, and F/G from d 0 to 7 more compared to blood cells. The greatest differences during this period occurred at the 5 and 7.5% inclusion levels. No differences in growth performance were detected from d 7 to 14. Therefore, when high levels (>5%) of blood products are used in nursery diets immediately after weaning, spray-dried blood meal provides some advantage over blood cells, but the advantage may be lost in the overall period.
Keywords: Swine; Nursery pig; Blood meal; Blood cells